Perancangan Interior Perpustakaan Daerah di Area Surabaya Barat - Hana Olivia Christy; Mariana Wibowo; Stephanie Melinda Frans (Intra, 2018)
In today's modern era, people tend to seek fun or entertainment in public space, such as a mall and many people who just follow the trend without noticing the important things like reading culture. Interior Design of Regional Library in West Surabaya Area aims to answer the phenomenon of many Indonesian people, especially in Surabaya who are lazy to read books. The specific target of this design is to provide facilities or accommodate the needs of the community to read. This design combines the local library with a mall so that presents a new concept to follow the lifestyle of today's society which is smart and stylish with futuristic style. The method in the design process is divided into 7 stages, namely: define research, ideate, prototype, selection, implementation, and learn. The result of the design using futuristic concepts are applied to the arrangement of furniture, furniture form, interior elements, floor patterns, ceiling pattern, and material used.